Clinical Characteristics of Peripherally Inserted Central Catheter in Critically Ill Patients - Hyoung-Joo Kim; Chang-Yeon Jung; Jung-Min Bae (Journal of Acute Care Surgery, 2019)
Purpose: Ensuring the stability of central venous catheter placement for treating patients hospitalized in an intensive care unit is very important. Although PICC requires an ultrasound and fluoroscopy machine, it is difficult to use a fluoroscopy machine for PICC insertion in the intensive care unit. This study analyzed the cases of the insertion of a PICC under ultrasonic guidance at the bedsides in the intensive care unit to determine the usefulness of PICC in the intensive care unit. Methods: A retrospective study was conducted on patients hospitalized in the surgical intensive care unit and received PICC using ultrasonography at their bedsides from October 2015 to January 2018. Results: One hundred and twenty patients were collected. The number of successful PICCs stood at 105 patients, which was equal to 87.5%. Among them, 65 and 55 cases had left and right insertion, respectively; the corresponding success rate was 81.8%, and 92.3%. No statistically significant difference in success rates was observed between the left and right, as well as in the success rates depending on the presence of shock, sepsis, acute kidney injury, and mechanical ventilation. In the failed 15 cases, seven cases were due to the course of the procedure and eight cases were confirmed have been malpositioned after insertion. Conclusion: PICC at the bedside in an intensive care unit is a safe method for central venous catheterization without severe complications and death. The insertion sites, left or right, are equally acceptable. Further study of the cases of malposition will be necessary.